The Development of Tri N-Based Interactive Learning Media to Improve Early Reading and Writing Skills of Elementary School Students - Yulianto, Eko; Sumarno, Sumarno; Buchori, Achmad (FKIP - Universitas Riau, 2025)
Early reading and writing skills are essential foundational competencies for students’ academic success. However, many elementary students still experience difficulties in recognizing letters, forming syllables, and constructing words due to the lack of engaging and contextual learning media. This study aims to develop and evaluate interactive learning media based on the Tri N principles (Niteni, Niroke, Nambahi) to improve students’ early reading and writing skills. The research used a Research and Development (R&D) approach with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study was conducted at SD Negeri 3 Tegaldowo, Rembang Regency, involving 36 students. Validation by material and media experts resulted in an average score of 52%, categorized as “fairly valid.” The practicality test showed an effectiveness rate of 44%. Pre-test and post-test assessments demonstrated an improvement in students’ reading and writing abilities, with an average N-Gain score of 57.76% in the moderate category. The significance test obtained a p-value of 0.000 for reading and 0.015 for writing, indicating that the media had a significant effect on learning outcomes. In conclusion, the Tri N-based interactive learning media effectively improve early reading and writing skills. Further development is recommended to refine the interface design and usability.